2011
DOI: 10.1111/j.1742-481x.2011.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

No need for biopsies: comparison of three sample techniques for wound microbiota determination

Abstract: The aim of the study was to compare three sampling techniques used in routine diagnostics to identify the microbiota in chronic venous leg ulcers. A total of 46 patients with persisting venous leg ulcers were included in the study. At inclusion, swab, biopsy and filter paper pad samples were collected. After 4 weeks, additional biopsy and filter paper pad samples were collected. Bacteria were isolated and identified at species level by standard methods. The most common bacterial species detected was Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 17 publications
7
37
0
4
Order By: Relevance
“…10,14 Fewer studies comment on anaerobes and the rigor of anaerobic cultivation methods vary widely, but even these studies disagree on the association of anaerobes with healing. 24,34,35,37 Results for Streptococcus species are most consistent, with most studies showing association with ulcers of increased size, longer duration, and healing delay. 24,[34][35][36] Interestingly, the studies that did not find associations between bacterial populations and healing were more likely to exclude patients with clinical signs of infection in the study design (Table 1 vs. Table 2).…”
Section: Presence Of Pathogenic Organismssupporting
confidence: 59%
See 2 more Smart Citations
“…10,14 Fewer studies comment on anaerobes and the rigor of anaerobic cultivation methods vary widely, but even these studies disagree on the association of anaerobes with healing. 24,34,35,37 Results for Streptococcus species are most consistent, with most studies showing association with ulcers of increased size, longer duration, and healing delay. 24,[34][35][36] Interestingly, the studies that did not find associations between bacterial populations and healing were more likely to exclude patients with clinical signs of infection in the study design (Table 1 vs. Table 2).…”
Section: Presence Of Pathogenic Organismssupporting
confidence: 59%
“…24,34,35 However, there are studies that associate S. aureus both with delayed healing 14,36 and smaller, healing ulcers. 23,37 Similarly, Pseudomonas species have been associated both with larger ulcers and delayed healing, 24,[34][35][36]38 whereas other (although fewer) studies have found that ulcers harboring Pseudomonas were more likely to heal normally. 10,14 Fewer studies comment on anaerobes and the rigor of anaerobic cultivation methods vary widely, but even these studies disagree on the association of anaerobes with healing.…”
Section: Presence Of Pathogenic Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the skin microbiome in UC was explored in 10 different studies, Table 1 37, 38, 39, 40, 41, 42, 43, 44, 45, 46. Current research into UC microbiome, comprises larger, longitudinal studies, compared to those in PV and HS.…”
Section: Resultsmentioning
confidence: 99%
“…However, this method is not available in all health establishments. 10 culture by swab is used universally due to the fact of being non-invasive, costly and not easy to perform. However, the results may indicate only colonization of the wound, as samples are not always properly obtained.…”
mentioning
confidence: 99%